2004
DOI: 10.1113/expphysiol.2004.027201
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide and thyroid gland: modulation of cardiovascular function in autonomic‐blocked anaesthetized rats

Abstract: We have previously reported that acute administration of N(G)-nitro-l-arginine methyl ester (L-NAME) increases the mean arterial pressure (MAP) and heart rate (HR) in autonomic-blocked (CAB) anaesthetized rats. In the present study we examined whether thyroid and adrenal glands are involved in these pressor and chronotropic responses. Sprague-Dawley rats were studied after bilateral vagotomy and ganglionic blockade with hexamethonium (10 mg kg(-1)), and stabilization of MAP with infusion of phenylephrine (PE) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 45 publications
(56 reference statements)
3
19
1
1
Order By: Relevance
“…In fact, it has been observed that in the rat with autonomic-blocked N G -nitro-Larginine methyl-ester (L-NAME) administration induces tachycardia, along with an increase in blood pressure. These effects are partially prevented by thyroidectomy and are not affected by adrenalectomy (Fellet et al, 2003(Fellet et al, , 2004. The tachycardic effects of NO inhibition in this rat model are in contrast to those observed by Ward and Angus (1993) in the rabbit.…”
Section: Nitric Oxide and Heart Ratecontrasting
confidence: 74%
“…In fact, it has been observed that in the rat with autonomic-blocked N G -nitro-Larginine methyl-ester (L-NAME) administration induces tachycardia, along with an increase in blood pressure. These effects are partially prevented by thyroidectomy and are not affected by adrenalectomy (Fellet et al, 2003(Fellet et al, , 2004. The tachycardic effects of NO inhibition in this rat model are in contrast to those observed by Ward and Angus (1993) in the rabbit.…”
Section: Nitric Oxide and Heart Ratecontrasting
confidence: 74%
“…Although NO was recognized primarily as a mediator of endothelial control of vascular smooth muscle, it is conceived as a paracrine autacoid involved in modulation of cardiac autonomic control and contractility (23). The mechanisms by which NO regulates heart contractility and contraction rate and the relations of the heart cycle to NO diffusion between mitochondria and cytosol are physiological processes that are starting to be understood.We have observed that N G -nitro-L-arginine methyl ester (L-NAME) administration to autonomic-blocked rats induces tachycardia, along with an increase in blood pressure, in a physiological process that is partially prevented by thyroidectomy and is not affected by adrenalectomy (18,19). It is well known that the heart is a target organ for thyroid hormones and that alterations in thyroid status influence cardiac contractile and electrical activities by a direct action of triiodothyronine (T 3 ) in cardiomyocyte receptors (16, 38).…”
mentioning
confidence: 98%
“…We have observed that N G -nitro-L-arginine methyl ester (L-NAME) administration to autonomic-blocked rats induces tachycardia, along with an increase in blood pressure, in a physiological process that is partially prevented by thyroidectomy and is not affected by adrenalectomy (18,19). It is well known that the heart is a target organ for thyroid hormones and that alterations in thyroid status influence cardiac contractile and electrical activities by a direct action of triiodothyronine (T 3 ) in cardiomyocyte receptors (16,38).…”
mentioning
confidence: 98%
“…According to our results, NO pathway would be involved in this mechanism. Thyroid hormones modulate NO steady-state level which may act as a messenger to modulate the mitochondrial bioenergetic function, resulting in an NO-mediated regulation of the heart pacemaker activity (Fellet et al 2004. Additionally, we demonstrated that hypothyroidism contributes in a differential way to ageing-induced changes in the myocardium and aorta tissues.…”
Section: Introductionmentioning
confidence: 86%